Use of 99m Tc in The Field of Radiofarmation: A Review - Kelutur, Faruk Jayanto; Abdul Holik, Holis (Biomedical Journal of Indonesia, 2021)
A B S T R A C TTechnetium-99m ( 99m Tc) has been applied in nuclear medicine as a radiopharmacyfor both diagnosis and therapy. 99m Tc is obtained from a 99 Mo/ 99m Tc (half-life 66 h)generator in the form of sodium pertechnetate (Na[ 99m TcO 4 ]) by decaying to 99 Tc for 6hours and emitting gamma energy rays (EÉ¤ = 140 keV). This radionuclide has anelectron configuration of 4d 5 5s 2 , which will form complexes with different ligandsand have oxidation rates from +1 to +7. The coordinated complex of technetium-99mhas been utilized in nuclear medicine in tissues and organs (thyroid, red and whiteblood cells, kidneys, brain, myocardial, and bone). The resulting kit production musthave based on Good Manufacturing Practice, which consists of batch planning,washing, sterilization of glassware and stopper, starting material, preparation oflarge quantities of the solution, sterile filtration, dispensing, crimping, a summary ofprocess control, quarantine, packaging and leaving the production premises.